ZNACZENIE I ROLA ŚWIADKÓW W LEGALIZACJI WCZESNOŚREDNIOWIECZNYCH DOKUMENTÓW NA PRZYKŁADZIE WYBRANYCH DOKUMENTÓW ZAKONU TEMPLARIUSZY - Henryk Streit (In Gremium. Studies in History, Culture and Politics, 2019)
THE ROLE AND IMPORTANCE OF THE WITNESSESOF THE LEGALISATION OF THE EARLY MIDDLE AGES’ RECORDSON THE BASIS OF THE KNIGHTS TEMPLAR’S DOCUMENTSS u m m a r yThis article describing the issue of the witnesses and their functions in the process of legalization ofmedieval documents also aim to show the rightness of the opinions about the authenticating functionsof testators created in the diplomatic doctrine.It also indicates that the very fact of the increase of the lawful role of a stamp on the turn of the 13the century does not allow to completely reject the list of witnesses as one of the means of authenticatinga document coexisting with the stamp.The analysis of a group of documents of an order of templars dated back to the years between1232-1308 seems to support the above-mentioned conclusions.Tłum. Henryk Streit